The enchanted hacienda - Cervantes, J. C. (Jennifer C.) (Park Row Books, 2023)
Harlow Estrada returns to the enchanted Hacienda Estrada, a family farm in Mexico where her mother, sisters, aunt and cousins harness the magic of charmed flowers, but when she's chosen to watch over the farm, she panics since she, herself, is magic-less, until she opens her heart to love and creativity.